Family support, anger and aggression in health workers during the first wave of the pandemic - Argyro Pachi; Maria Anagnostopoulou; Athanasios Antoniou; Styliani Maria Papageorgiou; Effrosyni Tsomaka; Christos Sikaras; Ioannis Ilias; Athanasios Tselebis (AIMS Public Health, 2023)
Introduction: Anger is considered as one of the basic human emotions, constituting the affective component of aggression. In the first year of the pandemic, the intense pressure on healthcare workers resulted in the deterioration of their psychosocial problems.